Beyond destruction and loss, urban resilience of the Historic Center of Managua - Suárez Bonilla, Brissa; De las Rivas-Sanz, Juan Luis (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
This article analyzes the factors that validate the resilient condition of the historic center of the city of Managua, a space that has suffered extraordinary events of destruction, but retains relevance in its urban system. With a synthetic narration of the facts, the conditions of a space of resistance in the face of adversity, capable of overcoming great impacts of natural and anthropic origin, are approached in an integrated manner. As expressions of this resilience, factors of location, morphology and management are identified that sustain the functional and symbolic capacity of the historic center, despite the loss of historic buildings and the disappearance of the scenography of the colonial heritage. To account for the potential of overcoming a history of destruction, abandonment and loss of this space, an eco-urban model of resilience is proposed, interpreted through adaptive cycles. In the background remains the hypothesis that historic centers are not only capable of overcoming adversities, but also play a vital role in the resilience of the urban system to which they belong.